Empathy and Depression Among Early Adolescents: The Moderating Role of Parental Support - Calandri, Emanuela; Graziano, Federica; Testa, Silvia; Cattelino, Elena; Begotti, Tatiana (Frontiers in Psychology, 2019)
Early adolescence is a period of development of emotional competence, but also of increasing vulnerability for the onset of depressive symptoms. While literature underscored that empathy promotes social relationships and psychological well-being over the life course, the possible role of high empathy levels as a risk factor for depression has been under investigated, especially among early adolescents. Moreover, although parenting practices are known to influence both empathy and depression in adolescence, few studies investigated if parenting moderates the relationship between empathy and depression. Therefore, the aims of the study were: 1) to investigate the relationships between affective and cognitive empathy and depression; 2) to investigate the moderating role of perceived paternal and maternal support on the associations between affective and cognitive empathy and depression; 3) to examine if the relationships among affective and cognitive empathy, maternal and paternal support and depression vary as a function of early adolescents’ gender. The study involved 386 Italian students aged between 12 and 14 (M age=13, SD=0.3; 47.9% girls) who completed an anonymous self-report questionnaire, including measures of cognitive and affective empathy, paternal and maternal support and depression. Results showed that with a mean level of affective and cognitive empathy, higher maternal support was related to lower depression for girls, whereas higher paternal support was related to lower depression for both boys and girls. Both maternal and paternal support moderated the relation between empathy and depression. In particular, maternal support moderated the non-linear relation between affective empathy and depression and the relation was further moderated by early adolescents’ gender: boys with low affective empathy reported lower depression in a context of high maternal support. Paternal support moderated the linear relation between cognitive empathy and depression, independently of early adolescents’ gender: boys and girls with high cognitive empathy reported higher depression in a context of low paternal support. The results of the study suggested that high empathy might be a risk factor for depression during early adolescence and mothers and fathers have a differential moderating role in relation to the affective and cognitive dimensions of empathy, also in relation to early adolescents’ gender.